PENYULUHAN KEBERSIHAN GIGI ANAK DI PEDUKUHAN KORIPAN - Nyka Dwi Febria; Dian Yosi Arinawati; Ika Andriani; Wustha Farani; Nabila Hasna Fitria (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2022)
Poncosari is a subdistrict which has 24 hamlets. Koripan is one of the hamlets in Poncosari. Koripan became a place for community service activities by KKN (Kuliah Kerja Nyata) students of group 109 Muhammadiyah University of Yogyakarta in 2022. Community service aims to increase public knowledge about dental and oral health of TPA (Taman Pendidikan Al-Quran) children in Koripan hamlet . The service method is carried out by providing dental and oral health counseling to children. This activity was carried out with the community and youth organizations as TPA mentors. The results obtained are an increase in children's knowledge about dental and oral hygiene. The conclusion from the community service carried out can increase children's knowledge about health.